Evaluation of the Effectiveness of the Implementation of Corporate Cultural Transformation with the Eight-Step Approach of Kotter (2014) and ADKAR Model (2012) Case Study on PT XYZ - Awang Setiawan; Fitriany Fitriany (Eduvest - Journal of Universal Studies, 2025)
PT XYZ is experiencing a decline in financial condition, leading to a downgrade in bond ratings due to the impact of the Covid-19 pandemic and project management errors. Based on the situation, the management of PT XYZ decided that a business transformation is necessary to improve the financial condition and ensure the company's sustainability. This business transformation consists of three transformations: cultural, people, and system. Cultural transformation becomes an important foundation for implementing other transformation programs. Evaluation of the implementation of cultural transformation is important to determine whether the transformation has been carried out effectively and sustainably. In this study, the evaluation of the cultural transformation program at PT XYZ uses two approaches: Kotter (2014)'s eight-step and ADKAR (2012). The use of both approaches is expected to result in a more comprehensive and in-depth evaluation. Kotter (2014)'s approach for conducting evaluations from an organizational perspective, and the ADKAR (2012) model for conducting evaluations from an individual perspective within the organization. This research uses a data triangulation approach, which includes data from company documentation studies, interviews (3 informants), and questionnaires (87 respondents). The study results show that overall, PT XYZ has carried out an effective cultural transformation in accordance with Kotter (2014)'s eight-step change model and the ADKAR (2012) model. However, there are several shortcomings that need attention and improvement, such as a top-down approach to vision, resistance due to additional workload, and benefit incentives that have not yet been directly felt by all employees.